2019
DOI: 10.1001/jamaophthalmol.2019.3392
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Spectrum of Pentosan Polysulfate Sodium–Associated Maculopathy

Abstract: IMPORTANCE A unique pigmentary maculopathy was recently described in 6 patients with long-term exposure to pentosan polysulfate sodium (PPS), a long-standing oral therapy for interstitial cystitis.OBJECTIVE To characterize the exposure characteristics and clinical manifestations of PPS-associated maculopathy. DESIGN, SETTING, AND PARTICIPANTSIn this multi-institutional case series, medical records of patients who exhibited the characteristic maculopathy in the setting of prior PPS exposure were retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
138
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 93 publications
(151 citation statements)
references
References 13 publications
5
138
1
1
Order By: Relevance
“…Five had fundus autofluorescence imaging done, of which 3 had retinal imaging findings consistent with prior reports of maculopathy in the context of long-term PPS exposure [ 2 , 3 ]. Outside of the chart review, one additional patient was referred (patient 4) and found to have findings consistent with PPS-associated maculopathy ( Table 2 ).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Five had fundus autofluorescence imaging done, of which 3 had retinal imaging findings consistent with prior reports of maculopathy in the context of long-term PPS exposure [ 2 , 3 ]. Outside of the chart review, one additional patient was referred (patient 4) and found to have findings consistent with PPS-associated maculopathy ( Table 2 ).…”
Section: Resultssupporting
confidence: 59%
“…In 2018, a case series of 6 patients demonstrated a possible link between long-term PPS exposure and pigmentary maculopathy [ 2 ]. In 2019, a multi-institutional case series identified 35 patients across 4 institutions with long-term exposure to PPS and pigmentary maculopathy [ 3 ]. An additional case report of maculopathy after long-term exposure to PPS was found to continue to progress for 6 years after discontinuation of this medication resulting in severe vision loss [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 Subsequent studies at multiple institutions have confirmed a strong association between long-term PPS use and the newly described maculopathy while also expanding our understanding of the phenotypic manifestations of this condition. [4][5][6] Fundus examination typically reveals nonspecific findings of macular pigment clumps amidst a background of yellowish subretinal deposits in early disease and retinal pigment epithelium (RPE) atrophy in late disease. 6 Multimodal fundus imaging demonstrates characteristic findings that localize disease to the RPE and RPE-photoreceptor interface and help differentiate this condition from other maculopathies such as age-related macular degeneration (AMD) and pattern dystrophy.…”
mentioning
confidence: 99%
“…6 Multimodal fundus imaging demonstrates characteristic findings that localize disease to the RPE and RPE-photoreceptor interface and help differentiate this condition from other maculopathies such as age-related macular degeneration (AMD) and pattern dystrophy. [6][7][8] In particular, fundus autofluorescence (AF) imaging reveals a characteristic pattern of densely packed hypo-and hyperautofluorescent spots that is typically centered on and involves the fovea and is highly symmetric between eyes. 9 Visual acuity in PPS maculopathy is typically normal until late disease in the setting of RPE atrophy.…”
mentioning
confidence: 99%
“…●IC/BPS: Most first‐ and second‐line treatments can be conducted via telemedicine including: patient education; self‐care counseling and behavioral modification (including diet changes); stress management techniques; and multimodal pain management using amitriptyline, cimetidine, hydroxyzine, or pentosan polysulfate 64 . Caution should be used when prescribing pentosan polysulfate as long‐term use has recently been associated with macular disease 65,66 . Self‐administered bladder instillations could be recommended for flares (EC). ●Dysmenorrhea and premenstrual syndrome: Most conservative treatment guidelines can be conducted via telemedicine, including lifestyle modifications (e.g.…”
Section: Resultsmentioning
confidence: 99%